Radio frequency identification (RFID) based electronic shopping trolley - Gwandira, Shepherd (Midlands State University, 2018)
There has been an emerging demand for quick and easy payment of bills in supermarkets. This project describes how to build an automated and time saving system for the world of retail which will make shopping experience impetuous, customer friendly and secure. In this dissertation, RFID based electronic is proposed that will be capable of generating a bill from the cart itself. The designed trolley helps the shop owner by reducing the shop assistances available on duty at one time the system will perform almost as a personal shop assistant for every single shopper in the shop, makes the best use of cart storage space The smart cart uses RFID technology for shopping and total. This innovative system will help the stores to see a rise in their sales along with delighting.